Purdue at 150 : A Visual History of Student Life - Hovde, David M.; Morris, Sammie (Sammie L.); Harmeyer, Neal; Harmeyer, Adriana, 1989- (Book collections on Project MUSE., 2019)
"Purdue at 150: A Visual History of Student Life by David M. Hovde, Adriana Harmeyer, Neal Harmeyer, and Sammie L. Morris tells Purdue's story through rare images, artifacts, and words. Authors culled decades of student papers, from scrapbooks, yearbooks, letters, and newspapers to historical photographs and memorabilia preserved in the Purdue University Libraries Virginia Kelly Karnes Archives and Special Collections. Many of the images and artifacts included have never been published, presenting a unique history of Purdue University from the student perspective. Purdue at 150 is organized by decade, presenting a scrapbook-like experience of viewing over 400 rare photographs, documents, and artifacts alongside critical contextual information. Each chapter provides a decadal historical sketch of Purdue University, offering insight into the institution's unique culture while incorporating campus responses to major national events such as world wars and the Great Depression. Spotlight sections highlight Purdue firsts, including the first graduates of programs, the growth and development of the international student population at Purdue, the creation of significant student organizations, and the foundations of both old and new campus traditions"--